Relationship between Body Mass Index (BMI) and Body Fat Level Against the Physical Fitness of Kabaddi Athletes during the Covid-19 Pandemic - Subekti, Maryoto (Journal of Physical Education Health and Sport, 2021)
Kabaddi is a traditional sport that originated in India. Kabaddi sport in Indonesia has grown rapidly since the appearance of this sport for the first time at the 2008 Asian Beach Games (ABG) in Denpasar Bali. With the outbreak of the COVID-19 pandemic, people's activities have been disrupted without exception for athletes' activities in exercising. Reflecting on the situation of the COVID-19 pandemic, coaches raise perceptions and concerns about the behavior of athletes who are not monitored due to the infrequent meetings that are usually held in joint training. This study aims to determine the relationship between body mass index and body fat levels on the physical fitness of Indonesian Kabaddi Athletes. The research sample consisted of 24 Indonesian Kabaddi Male Athletes. The results showed that the simultaneous relationship between body mass index and body fat content on physical fitness was not significantly correlated as indicated by the value of p 0.05. Based on this, it can be concluded that there is no significant relationship between body mass index and body fat content on the physical fitness of Indonesian Kabaddi Athletes.